Culinary tourism – innovations in farm-to-table practices for sustainable experiences - Stoica, Mariana (CEP USM, 2024)
This article delves into the relationship between culinary tourism and sustainability, focusing on how farm-to-table innovations can elevate tourist experiences while promoting environmental and social responsibility. It examines how sustainable dining can serve as a platform to connect tourists with local food cultures and production practices.
Keywords: culinary tourism; sustainability; farm-to-table; local producers; innovative practices; environmental responsibility